The effect of creative-collaborative problem solving to enhance cognitive ability and creative thinking skills in term of facilitating pre-service primary teachers’ solving thermal problems - D Maulana; A Suhandi; E Syaodih; B Maftuh; H Handayani; A Samsudin (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Currently cognitive ability and creative thinking skills have been being warm issuesand they need to be developed to solve the problems regarding to the thermal problems. Thisresearch aims to facilitate the creative-collaborative problem solving to enhance cognitiveability and creative thinking skills. Fourths pre-service primary teachers have been involved into pre-experimental method with pre- and post-tests design (5 male and 12 female). Theinstruments about creative thinking skills and cognitive skills have already developed tomeasure the creativity and cognitive ability of students. The data show that the in-serviceprimary teachers have “high” about 76.47% for creative thinking skills and “moderate” level(33.33%) for cognitive ability as well. In conclusion, creative-collaborative problem solving isable to enhance effectively cognitive ability and creative thinking skills on thermal concepts(temperatures, heat transfer and matter change).